Pengaruh Komunikasi, Kompensasi Finansial dan Kompetensi Terhadap Kinerja Karyawan - Putra, Agus Hendra; Supartha, I Wayan Gede (E-Jurnal Manajemen; Vol 3 No 10 (2014), 2014)
Normal 0 false false false IN X-NONE X-NONE Employee’s performance is process that done by employee to reach the company’s goals. So its employee has a high performance, company should notice all factors that affect employee’s performance. This research has purpose to know communication effect, financial compensation, and competition to employee’s performance. This research was done in Hotel Agung Cottages Kuta, Badung with respondent amount is 60 respondents. Data collection was done by interview, observation, and questionnaire and its result tested by F test and t test also standardized coefficient beta which manage by software statistical of social science (SPSS) program for windows. This communication variable analysis, financial compensation, and competition by simultaneous has significant effect to employee’s performance by 75,8 percent contribution. Partially variable is also has significant effect and positive to employee’s performance. Financial compensation variable is variable that has dominant effect to employee’s performance and Hotel Agung Cottages is expected to notice communication, financial compensation, and competition so it can increase its employee’s performance /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: employee’s performance, communication, financial compensation, and competition